Influence of Urea Content in Deep Eutectic Solvents on Thermoplastic Starch Films’ Properties - Magdalena Zdanowicz (Applied Sciences, 2023)
The goal of the study was to prepare deep eutectic solvents (DESs) with different urea (U) contents and apply them as potato-starch plasticizers to investigate the influence of various DES compositions on the physicochemical properties of thermoplastic starch (TPS) obtained via thermocompression. As hydrogen bond acceptors, quaternary ammonium compounds, choline chloride (CC) and betaine (B-anhydrous and monohydrate) were used. The molar ratios of CC or B to U were 1:2, 1:3, 1:4 and 1:5. Before starch processing, the DESs were thermally characterized (DSC, TGA). The increase in U content in the eutectics led to higher phase-transition temperatures and lower thermal stability. The influence of the DESs on thermocompressed TPS mechanical (tensile test) and thermal–mechanical (DMTA) properties, morphology (XRD and FTIR), sorption/dissolution behavior and surface contact angle was investigated. The mechanical tests revealed that the increase in U led to higher elongation at break and a highly amorphous structure. The FTIR results indicated that the starch underwent some carbamation derivatization with the presence of B. The DESs with high U content plasticized starch effectively; therefore, preliminary extrusion tests for starch were performed with selected CC and B-based DES with the molar ratio of 1:5.